2017
DOI: 10.1016/j.patrec.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

LaBGen: A method based on motion detection for generating the background of a scene

Abstract: Given a video sequence acquired with a fixed camera, the generation of the stationary background of the scene is a challenging problem which aims at computing a reference image for a motionless background. For that purpose, we developed our method named LaBGen, which emerged as the best one during the Scene Background Modeling and Initialization (SBMI) workshop organized in 2015, and the IEEE Scene Background Modeling Contest (SBMC) organized in 2016. LaBGen combines a pixel-wise temporal median filter and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…In our previous works related to LaBGen [10], we have shown that, surprisingly, the frame difference background subtraction algorithm is the most effective motion detection, on average, for our background generation framework. Compared to other background subtraction algorithms, the main specificity of the frame difference algorithm is that it detects motion between two frames without relying on additional past frames.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In our previous works related to LaBGen [10], we have shown that, surprisingly, the frame difference background subtraction algorithm is the most effective motion detection, on average, for our background generation framework. Compared to other background subtraction algorithms, the main specificity of the frame difference algorithm is that it detects motion between two frames without relying on additional past frames.…”
Section: Introductionmentioning
confidence: 87%
“…The LaBGen background generation method, extensively described in [10], combines a pixel-wise median filter and a patch selection mechanism based on a motion detection performed by a background subtraction algorithm. It is composed of the five following steps, which are illustrated in Fig.…”
Section: Short Description Of the Principles Of Labgenmentioning
confidence: 99%
See 1 more Smart Citation
“…Background generation [18,100,129] (also called background initialization [89,91] [ 92,176], background estimation [38,70], and background extraction [198]) regards the initialization of the background. Generally, the model is often initialized using the first frame or a background model over a set of training frames which contain or do [93] and LaBGen [105,106,107] that are based on robust PCA [20,21] and the robust estimation of the median, respectively. Practically, the main challenge is to obtain a first background model when more than half of the training contains foreground objects.…”
Section: Background Generationmentioning
confidence: 99%
“…We additionally devised a method for detecting brood cells in a colony. We first used a background extraction method 71,72 applied to a range of images spanning 12 h. One background image was generated for each consecutive 12 h (Supplemental Movie M1). We then adopted our bee annotation tool (https://github.com/oist/DenseObjectAnnotation) to annotate center points of each brood cell in the generated background images.…”
Section: Brood Detectionmentioning
confidence: 99%